Evaluation of stress–relieving heat treatment on mechanical properties and microstructure of friction-welded JIS S45C steel - Susanto, Alexander Eka; Haryadi, Gunawan Dwi; Haryanto, Ismoyo; Sulardjaka, Sulardjaka; Nugroho, Sri; Ekaputra, I Made Wicaksana (Jurnal Polimesin, 2025)
This research evaluates the effect of stress-relieving post-weld heat treatment (PWHT) on the mechanical properties and microstructure of friction-welded JIS S45C steel joints. The PWHT was conducted at 500 °C for 1 hour. Tensile and Vickers microhardness tests were performed on both as-welded and heat-treated specimens. The tensile tests showed that fracture consistently occurred in the base metal, confirming good weld quality. Stress-relieved specimens showed a 3% increase in elongation compared to the as-welded condition, indicating improved plasticity. The Vickers microhardness tests revealed around 10% decrease in hardness at the weld center zone (from 293 HV to 267 HV) and heat-affected zone (from 245 HV to 224 HV) after treatment. Metallographic observation indicated coarsening of the pearlite phase due to thermal exposure.